If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 23 = 14x + -27 Reorder the terms: 23 + 4x = 14x + -27 Reorder the terms: 23 + 4x = -27 + 14x Solving 23 + 4x = -27 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 23 + 4x + -14x = -27 + 14x + -14x Combine like terms: 4x + -14x = -10x 23 + -10x = -27 + 14x + -14x Combine like terms: 14x + -14x = 0 23 + -10x = -27 + 0 23 + -10x = -27 Add '-23' to each side of the equation. 23 + -23 + -10x = -27 + -23 Combine like terms: 23 + -23 = 0 0 + -10x = -27 + -23 -10x = -27 + -23 Combine like terms: -27 + -23 = -50 -10x = -50 Divide each side by '-10'. x = 5 Simplifying x = 5
| 4x-23=14x-27 | | 6x+y=31.5 | | 5x+1=-3x-15 | | 12x-8y=32 | | y/2-y/6=9 | | y=4/5x-1 | | -0.43p=36 | | 5x^2-x^0=80 | | 8/8.5*X=8 | | y=1/5x+4 | | 2x-1=15+5x | | -6t+g=6 | | -6t+6=6 | | -0.0912+0.96v=-0.168 | | -0.0912+0.96=-0.168 | | 3t+4g=6 | | 3t+2d=52 | | 4x^3+6x^2-2x+9=0 | | 3x-6(2x-10)=159 | | 3t+2d=62.5 | | y=y(600-3y) | | 22x+13=-5-7x | | 8(4x-5)=9(x-6)-5 | | -84-10x=8+24 | | 86x-3x=10x+21 | | 6B=420 | | 3x-1=3x+8 | | -3z-6=0 | | 8=-8x-8 | | 5(0)-y=-7 | | -9=-5x+19 | | 9e^3x+2=54 |